The importance of wind as a driver of earthen heritage deterioration in dryland environments - Richards, J; Viles, H; Guo, Q (Elsevier, 2020)
Dryland regions are exposed to extreme environmental conditions that create hotspots of weathering and erosion. Many earthen heritage sites are located in these dryland regions and experience extensive deterioration driven by interactions with environmental processes, however previous research has focused largely on the role of rain as a driver of deterioration. This study combines approaches from geomorphology with understandings of earthen materials from heritage science to investigate the relative importance of wind and rain in driving earthen heritage deterioration in drylands. We use geomorphological signatures to infer the environmental histories of earthen walls with a range of known ages at Suoyang Ancient City, China, using semi-quantitative deterioration assessments. We find rain-driven deterioration features to be associated with the loss of larger volumes of material and to have higher persistence than wind-driven deterioration features. However, we argue that the high frequency nature of wind events means that wind is an important initiator of deterioration across the site. In addition, walls exposed to the prevailing wind are dominated by wind-driven deterioration features. Outcomes from this study present an opportunity for earthen heritage conservation to investigate potential strategies to minimise wind speed at earthen heritage sites in drylands.